2018
DOI: 10.1128/jvi.00902-18
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Stress Granule Formation by Middle East Respiratory Syndrome Coronavirus 4a Accessory Protein Facilitates Viral Translation, Leading to Efficient Virus Replication

Abstract: Stress granule (SG) formation is generally triggered as a result of stress-induced translation arrest. The impact of SG formation on virus replication varies among different viruses, and the significance of SGs in coronavirus (CoV) replication is largely unknown. The present study examined the biological role of SGs in Middle East respiratory syndrome (MERS)-CoV replication. The MERS-CoV 4a accessory protein is known to inhibit SG formation in cells in which it was expressed by binding to double-stranded RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 66 publications
2
107
1
1
Order By: Relevance
“…Indeed, CoV nsp1 with its host-shut-off activities (see above) is a likely candidate viral protein that could play a role. A later report by Nakagawa et al [101] however showed that the ORF4 MERS-CoV mutant virus did induce stress granules in another cell line (Hela/ CD26), and also a virus mutant in which 4a alone was removed was not able to suppress SG formation in these cells. This suggests that the activity of 4a, and possibly other stress granule-inhibiting MERS-CoV proteins, may differ per cell line, or that cell lines differ in the activity of their antiviral pathways.…”
Section: Manipulation Of Stress Granule Formationmentioning
confidence: 90%
“…Indeed, CoV nsp1 with its host-shut-off activities (see above) is a likely candidate viral protein that could play a role. A later report by Nakagawa et al [101] however showed that the ORF4 MERS-CoV mutant virus did induce stress granules in another cell line (Hela/ CD26), and also a virus mutant in which 4a alone was removed was not able to suppress SG formation in these cells. This suggests that the activity of 4a, and possibly other stress granule-inhibiting MERS-CoV proteins, may differ per cell line, or that cell lines differ in the activity of their antiviral pathways.…”
Section: Manipulation Of Stress Granule Formationmentioning
confidence: 90%
“…4b i ). Manipulation of SG and related RNA biology is common among coronaviridae 34 36 and stress granule formation is thought to be a primarily antiviral response. The promotion of G3BP aggregation by eIF4A inhibitors 28 , 37 may partially explain their antiviral activity (see below).…”
Section: Mainmentioning
confidence: 99%
“…classical being the protein kinase R (PKR)-triggered pathway. PKR regulates the transcription and translation of cells through its phosphorylation initiation factor eIF2α, which plays an important role in cell growth (14). After viral infection, PKR binds to viral double-stranded RNA (dsRNA), which activates the autophosphorylation of the kinase.…”
mentioning
confidence: 99%